1999
DOI: 10.1590/s0100-879x1999001200019
|View full text |Cite
|
Sign up to set email alerts
|

Binding sites and actions of Tx1, a neurotoxin from the venom of the spider Phoneutria nigriventer, in guinea pig ileum

Abstract: Tx1, a neurotoxin isolated from the venom of the South American spider Phoneutria nigriventer, produces tail elevation, behavioral excitation and spastic paralysis of the hind limbs after intracerebroventricular injection in mice. Since Tx1 contracts isolated guinea pig ileum, we have investigated the effect of this toxin on acetylcholine release, as well as its binding to myenteric plexus-longitudinal muscle membranes from the guinea pig ileum. [ 125 I]-Tx1 binds specifically and with high affinity (K d = 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…Nonetheless, PnTx1 awaits further investigation in order to elucidate its Cav channel interaction. Using similar competitive binding experiments it was shown that 125 I-PnTx1 partially blocked the PhTx2 induced activity in myenteric plexus-longitudinal muscle preparations (Santos et al, 1999). Since PhTX2 is the fraction that contains mainly sodium channel toxins, this observation hinted towards an activity of PnTx1 on Nav channels.…”
Section: Phtx1mentioning
confidence: 84%
See 2 more Smart Citations
“…Nonetheless, PnTx1 awaits further investigation in order to elucidate its Cav channel interaction. Using similar competitive binding experiments it was shown that 125 I-PnTx1 partially blocked the PhTx2 induced activity in myenteric plexus-longitudinal muscle preparations (Santos et al, 1999). Since PhTX2 is the fraction that contains mainly sodium channel toxins, this observation hinted towards an activity of PnTx1 on Nav channels.…”
Section: Phtx1mentioning
confidence: 84%
“…fraction PhTx3, which contains several calcium channel modulating peptides. However, labeled PnTx1 did not compete with ω-conotoxin GVIA, a calcium channel inhibiting toxin isolated from cone snail venom (Santos et al, 1999). This rather contrary result was later attributed to the presence of a small contamination with PnTx3-3.…”
Section: Phtx1mentioning
confidence: 92%
See 1 more Smart Citation
“…The cyanosis seen in some patients probably reflects a combination of respiratory disturbances, such as pulmonary edema resulting in poor oxygenation, cardiac failure/shock, and, more rarely, marked peripheral direct vasoconstriction. Vomiting and abdominal pain may indicate a stimulatory effect on the gastrointestinal tract, possibly through a combination involving the activation of autonomic pathways, the release of neuropeptides, direct activation of smooth muscle by toxins such as PhTx1 (Tx1) (Santos et al 1999), and the low molecular mass fraction of the venom that contains tachykinin-like venom peptides (Pimenta et al 2005). In rats, PNV delays gastric emptying partly through a catecholaminemediated mechanism (Bucaretchi and Collares 1996).…”
Section: Other Manifestationsmentioning
confidence: 99%
“…They are similar in size to scorpion a and b toxins that also target Na V channels (Rodriguez de la Vega and Possani, 2005), but they have no sequence homology and contain a larger number of disulfide bonds. Preliminary studies suggested that m-CNTX-Pn1a might target vertebrate Ca V channels (dos Santos et al, 1999Santos et al, , 2002) but more recent studies have shown that it is a state-dependent blocker of rat Na V 1.2 that binds in the vicinity of channel site 1 (Martin-Moutot et al, 2006). The high level of sequence identity suggests that all members of this family will have the same pharmacology.…”
Section: Nasptx Familymentioning
confidence: 99%